SYNTHESIS AND ELECTRONIC ABSORPTION SPECTRA OF SOME METHOXY HALF-ANALOGUE OF MICHLER'S HYDROL BLUE (Journal of Sciences, Islamic Republic of Iran)
The present work comprises the synthesis of one series of diarylmethane dyes containing one or more terminal methoxy substituents together with a variable tertiary amino group. The electronic absorption spectra of the dyes have been determined. As the conjugation of the terminal nitrogen atom improves in the sequence NMez > Kairoline > Julolidine, a progressive hypsochromic shift is observed